Modelling of solid / liquid fractionation of trace metals for suspended sediments according to the hydro-sedimentary conditions of rivers - Application to 137Cs in the Rhône River (France). (November 2021) - Tomczak, Wirginia; Boyer, Patrick; Eyrolle, Frederique; Radakovitch, Olivier; Krimissa, Mohamed; Lepage, Hugo; Amielh, Muriel; Anselmet, Fabien
Abstract: The behavior and impact of trace metals discharged into rivers depend on their solid/liquid fractionation and the fate of these two phases according to hydro-sedimentary processes. The solid/liquid fractionation depends on many environmental factors which imply uncertainties of several orders of magnitude in the evaluation of the partition coefficients, whether by geochemical modelling, in situ measurements or sorption-desorption experiments. In this context, this paper presents a model of solid/liquid fractionation of trace metals with suspended sediments in rivers which integrates the hydro-sedimentary conditions and the properties of the watershed. Its comparison with the 137 Cs concentrations measured in the Rhône River (France) thanks to monitoring shows that the solid/liquid fractionation of 137 Cs with suspended sediments in rivers depends on chemical processes but also and above all on variations in water flow rate, size and load of suspended sediments and the balance between anthropogenic discharges and the average trace metal content of soils in the watershed. Highlights: Kd modelling according to hydro-sedimentary conditions. Particle size effect on Kd . Geochemical background effect on Kd . Colloidal pumping effect on Kd .